(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years IoT is becoming the trending technology which is playing a major role in business, health care, military applications. Wireless communications are highly vulnerable to security threats as anything connected to internet are prone to cyberattacks and place for hackers. Various challenges in IoT are causing security threats and not ensuring End-to-End encryption during transmission of information. Currently most IoT devices use default login credentials and not secured with better configurations and protocols which paves way for cyberattacks. Advanced security standards cannot be employed for all IoT devices. This paper proposed a secure authentication protocol for the IoT platform for ensuring security among IoT devices which keeps track of security threats. An evaluation of the proposed protocol is presented which proves that the protocol is able to address various security threats.